ROLE OF HYPEROXIA IN THE TREATMENT OF COVID-19 AND OTHER PNEUMONIAS (Vietnam Journal of Community Medicine, 2026)
Objectives: Synthesize contemporary evidence on the benefits and harms of hyperoxia-supraphysiologic arterial oxygen caused by high inspired oxygen-in adults with COVID‑19 and other pneumonias, and translate findings into pragmatic oxygen targets.Methods: We consulted WHO and NIH living guidelines, professional society guidance, randomized trials of acute hypoxemic respiratory failure (including COVID‑19), and mechanistic reviews through October 17, 2025. Outcomes included mortality, organ dysfunction, ventilator‑ and oxygen‑free days, and oxygen‑related adverse events.Results: Guidance converges on titrated oxygen that avoids both hypoxemia and sustained hyperoxia, typically targeting SpO2 92-96% for most adults and 88-92% for those at risk of hypercapnic respiratory failure. Large ICU trials (HOT‑ICU) and a COVID‑19-specific trial (HOT‑COVID) show no survival advantage with higher PaO2 targets (~90 mmHg) compared with lower targets (~60-70 mmHg). Mechanistic and clinical data link hyperoxia to oxidative lung injury, absorption atelectasis, impaired microcirculation, and CO2 retention in predisposed patients.Conclusions: In COVID‑19 and other pneumonias, liberal oxygen strategies aiming for supranormal saturations confer no mortality benefit and may cause harm. Practice should prioritize goal‑directed, conservative oxygenation-aim for SpO2 92-96% (or 88-92% in CO2 retainers), reassess frequently, and wean FiO2 early with appropriate PEEP.
Keywords: Hyperoxia, oxygen therapy, COVID‑19, pneumonia, oxygen targets, ICU.